2023
DOI: 10.3390/ijerph20020974
|View full text |Cite
|
Sign up to set email alerts
|

Self-Myofascial Release of the Foot Plantar Surface: The Effects of a Single Exercise Session on the Posterior Muscular Chain Flexibility after One Hour

Abstract: This study evaluated the effects of a single exercise session of Self-Myofascial Release (SMR) on the posterior muscular chain flexibility after one hour from the intervention. Thirty-six participants performed SMR using a rigid ball under the surface of both feet. Participants were tested with the Sit and Reach (S&R) test at four different times: before (T0), immediately after (T1), 30 (T2), and 60 (T3) minutes after the SMR intervention. The sample (n = 36) was categorized into three groups: (1) flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The ROM of flexion of the hip, knee, and ankle joints is important for the quality of the squat performance. The obtained results can be compared with the research in which the application of SMR plantar facials managed to increase the posterior muscular chain flexibility ( 33 ). The authors explain this phenomenon by the fact that the plantar fascia is the most distal part of the muscle chain, and that applying pressure on it stimulates mechanoreceptors that enable relaxation of the entire chain ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ROM of flexion of the hip, knee, and ankle joints is important for the quality of the squat performance. The obtained results can be compared with the research in which the application of SMR plantar facials managed to increase the posterior muscular chain flexibility ( 33 ). The authors explain this phenomenon by the fact that the plantar fascia is the most distal part of the muscle chain, and that applying pressure on it stimulates mechanoreceptors that enable relaxation of the entire chain ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The landmarks for pelvic parameters during forward bending were defined as reported by Carregaro et al [ 53 ]. Since adolescents with hyperkyphosis show a low level of flexibility across the muscular posterior chain, sacral inclination and hip position were calculated to investigate pelvic displacement in the sagittal plane [ 6 , 33 , 48 ]. PG Sacrum inclination evidenced a significant correlation with SM trunk inclination during bending, and linear regression reported that trunk bending added to hip bending explained 80.4% of SM variability in relation to this parameter (first model).…”
Section: Discussionmentioning
confidence: 99%
“…Within this scenario, it could be very interesting for professionals to use photogrammetry, the easiest and cheaper way, as a global screening tool to detect in advance the signs of a spine misalignment, with particular regard to the kyphosis curvature. Considering the whole body as a kinetic chain [ 33 ], and that photogrammetry could easily measure the alignment of the whole body with good validity and reliability [ 32 ], a relation could be hypothesized between thoracic spine behavior and one or more photogrammetric measurements of body posture. Although radiographic and photogrammetric procedures have been previously investigated in order to quantify thoracic kyphosis and lumbar lordosis [ 34 , 35 ], the comparison between Spinal Mouse ® evaluation and photogrammetry is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Testing procedures were carried out in a Sport Performance Laboratory at a mean temperature of 19 °C and a mean relative humidity of 51%, and each subject was tested at the same time of the day, avoiding any circadian effect [ 38 , 39 , 40 ]. The first day of the training period, all participants were tested for anthropometric measures aiming to find out the three different poles’ length: classical, reduced and increased length 65%, 55% and 75% of the participant’s height, respectively.…”
Section: Methodsmentioning
confidence: 99%